Aluminum Craftsmen's Income to Meet the Family Economic Needs in Ohoitahit Village, Dullah Utara District, Tual City - Sether, Rasni; Lasaiba, Mohammad Amin; Riry, Roberth Berthy (JENDELA PENGETAHUAN, 2022)
potential to improve the economy and fulfill the livelihood needs of the local community. However, this sector faces several obstacles, such as limited human resources, simple equipment, and lower product quality and quantity compared to industry standards. Nevertheless, aluminum artisans can fulfill their families' clothing, food, and housing needs, as well as provide attention to education and healthcare for family members. Based on the findings of this research, it can be concluded that the household aluminum craft industry plays a significant role in improving the welfare of households in Ohoitahit Village. Increased government and relevant party support is expected to assist artisans, thus enabling this sector to contribute significantly to the local economy and community welfare.